Javanese Cultural Epistemology of Raden Muhammad Adnan’s Thoughts in Tafsir Al-Qur’an Suci Basa Jawi - Muhamad Dani Habibi; Arpandi Arpandi; Asep Kusmawan; Ahmad Fauzan (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This paper discussed the epistemology of Javanese interpretation, studying the thoughts of Raden Muhammad Adnan through Tafsir Al-Qur’an Suci Basa Jawi book. This tafsir book, published in the 20th century, has become an essential document in studying the science of the Qur'an and tafsir. This phenomenon is because the book was written by the first rector of the Sunan Kalijaga State Islamic University, Yogyakarta. The book was written in Javanese and lived in the New Order era, coupled with the involvement of power, which is why the authors study it further. Therefore, we need to know the background of the book's writing, the exegete's scientific genealogy and the book's methods and presentation to increase the local interpretation values. Thus, the authors used qualitative research methods and an interpretive epistemological approach. In the study of epistemology, seeking knowledge focuses on three aspects: the source of knowledge, the validity of the truth and the implications of the fact of the interpreter's knowledge. The transformation of science impacted the Basa Jawi interpretation book, which emphasizes local Javanese cultural and mystical approaches.